Pengembangan Pariwisata Berbasis Kearifan Lokal Melalui Gelaran Batu Flora Festival - Risna Amalia Ulfa (Syntax Idea)
Local wisdom, encompassing values, traditions, cultural heritage, and traditional skills in agriculture, crafts, or local arts, has become a highly sought-after tourist attraction with economic value. Various cultures and local wisdom in the city of Batu, packaged in festivals, have emerged as an alternative Destination Tourism Area (DTW) in this City of Flowers. Since its inception in 2007, the Batu Flora Festival (BFF) has become a regular annual event as part of the Batu City anniversary celebrations, attracting thousands of visitors. This fact underscores the importance of tourism based on local wisdom through flower and ornamental plant festivals as a viable alternative for tourism development, not only for the local market but also as a significant promotional tool to introduce Batu City internationally. The aim of this research is to provide recommendations for relevant stakeholders by identifying and determining whether the implementation of BFF is an effective strategy in developing and promoting Batu City with its unique local wisdom potential. The research method employed is qualitative analysis through literature review and information gathered from various media related to the Batu Flora Festival. The analysis method used is the Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. A STRUCTURED SWOT analysis is employed to assess the potential and issues in local wisdom-based tourism in Batu City through the Batu Flora Festival, encompassing internal and external potentials and issues.